Corticosteroids significantly increase cystatin C levels in the plasma by promoting cystatin C production in rats. (1st January 2019) - Zhu, Xiao-Ran; Ge, Ning; Wang, Yu; Zhai, Jian-Long; Liu, Chao
Abstract: Background: Several studies have shown that non-renal factors such as corticosteroids may increase plasma cystatin C levels without affecting kidney function. However, the mechanisms underlying this are unclear. We hypothesized that corticosteroids may increase cystatin C levels in the plasma by promoting its production in tissues. In the present study, we aimed to test our hypothesis in rats by investigating the effect of corticosteroids on cystatin C production in tissues and the glomerular filtration rate (GFR), as measured by the gold standard method (i.e., inulin clearance). Results: Dexamethasone treatment was associated with much higher concentrations of cystatin C in all organ tissue homogenates tested. Dexamethasone increased plasma cystatin C levels in rats, without any decrease in renal inulin clearance. The impact of dexamethasone on plasma and organ tissue cystatin C levels was abolished by RU486, indicating the effect was glucocorticoid receptor-mediated. Conclusions: Our study provides direct evidence that corticosteroids may increase cystatin C levels in the plasma by promoting its production, without any decrease in GFR.